2011
DOI: 10.1126/science.1206583
|View full text |Cite
|
Sign up to set email alerts
|

Increasing N Abundance in the Northwestern Pacific Ocean Due to Atmospheric Nitrogen Deposition

Abstract: The relative abundance of nitrate (N) over phosphorus (P) has increased over the period since 1980 in the marginal seas bordering the northwestern Pacific Ocean, located downstream of the populated and industrialized Asian continent. The increase in N availability within the study area was mainly driven by increasing N concentrations and was most likely due to deposition of pollutant nitrogen from atmospheric sources. Atmospheric nitrogen deposition had a high temporal correlation with N availability in the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
211
2
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 249 publications
(221 citation statements)
references
References 32 publications
7
211
2
1
Order By: Relevance
“…Over the past 150 years, the deposition of N compounds is estimated to have doubled [Duce et al, 2008], while the deposition of P species has remained relatively steady [Baker et al, 2003;Mahowald et al, 2008]. Consequently, recent modeling studies predict an atmospheric deposition-driven increase in P depletion in surface waters of some ocean regions relative to preindustrial times [Kanakidou et al, 2012;Kim et al, 2011;Krishnamurthy et al, 2007Krishnamurthy et al, , 2009Zamora et al, 2010]. However, the atmospheric fluxes of P to the ocean are poorly characterized compared to N deposition fluxes.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past 150 years, the deposition of N compounds is estimated to have doubled [Duce et al, 2008], while the deposition of P species has remained relatively steady [Baker et al, 2003;Mahowald et al, 2008]. Consequently, recent modeling studies predict an atmospheric deposition-driven increase in P depletion in surface waters of some ocean regions relative to preindustrial times [Kanakidou et al, 2012;Kim et al, 2011;Krishnamurthy et al, 2007Krishnamurthy et al, , 2009Zamora et al, 2010]. However, the atmospheric fluxes of P to the ocean are poorly characterized compared to N deposition fluxes.…”
Section: Introductionmentioning
confidence: 99%
“…diversity of the terrestrial ecosystems (Stevens et al, 2004;Clark and Tilman, 2008;Bobbink et al, 2010;Jiang et al, 2010;Kim et al, 2011). Both large-scale field survey and manipulated experiments to simulate N deposition have shown that N deposition has driven significant reductions in plant species richness in different grassland ecosystems (Stevens et al, 2004;Suding et al, 2005;Bai et al, 2010;Tilman, 2008, Dupre et al, 2010;Van Den Berg et al, 2011).…”
Section: Q-y Tian Et Al: Disruption Of Metal Ion Homeostasis In Soilsmentioning
confidence: 99%
“…As inferred from extremely high organic matter inputs to the bottom layer, a 'micro reducing environment̓ may be formed in the bottom layer (Wolgast et al 1998), enabling an upward extension of denitrifying bacterial activity from the sediments to the bottom waters above. Recent increases in atmospheric nitrogen deposition flux to the EJS (Kim et al 2011), warming of the water column (Gamo et al 2001;Kim et al 2001Kim et al , 2004Min and Kim 2006), oxygen content decreases (Kim and Kim 1996;Chen et al 1999;Gamo 1999;Kang et al 2004), and high deposition rates of organic matter (Cha et al 2007;Tishchenko et al 2007;Lee et al 2008Lee et al , 2010Hyun et al 2010) might have created a favorable environment for denitrification in the bottom layer at the two basins in the EJS in recent years.…”
Section: Extended Benthic Denitrification To Bottom Waters Vs 'Aerobmentioning
confidence: 99%